Brazilian democratic transition and the student movement at the State University of Ceará (1979-1989) (Tempo e Argumento, 2024)
This article addresses the 1980s Student Movement at the State University of Ceará, Brazil. Contextualized in the final years of the Civil-Military Dictatorship and onset of Brazil’s redemocratization, this study examined documents produced by student bodies, heard from eight Central Student Directorate (DCE) former leaders, and some of the main political currents active at the university at the time. It dialogues with Oral History’s theoretical and methodological foundations and gathers the accounts of these former activists about the political context they faced at the University and excerpts of their activism during the period.
Keywords: student movement; democratc transition; UECE